ANALISA KARAKTERISTIK PARKIR DAN PENGARUH ON STREET PARKING TERHADAP KINERJA LALU LINTAS (Studi Kasus Pada Ruas Jalan Kartini Kota Salatiga) - Zulvia, Avita; Rizani, Mohammad Debby; Permata Suwandi, Putri Anggi (Universitas PGRI Semarang, 2022)
AbstractThe space are available for parking vehicles on the roadside in the downtown area and along main highways is carried out with still restrictions and controls and arrangements or is often called on-street parking (Clarkson Grg Lesby and Bary Hicks, 1988). This research is motivated by the problem of less than optimal traffic performance caused by the presence of on street parking on the bicycle lane on Jalan Kartini, Salatiga City. In overcoming these problems, it is necessary to analyze the characteristics of parking and the effect of on street parking along Jalan Kartini, Salatiga City. The method used in this study is a quantitative descriptive approach. Collecting data obtained from interviews, field notes, personal documentation, researcher notes, and other resident documents. This study shows that parking characteristics and the effect of on street parking on traffic performance on Jalan Kartini, Salatiga City, for parking duration are categorized as Category I and high turnover which means short duration, generally parking vehicles are less than one hour with short parking durations. for parking in shopping centers, with a road capacity of 2489.22 smp/hour, a free-flow speed of 37.665 km/hour and a level of service belonging to the Level Of Service (LOS) B category (0.20-0.44) with stable flow characteristics, speed is slightly limited by traffic, driver can still freely choose his speed.Keywords: parking, on street parking, characteristics